A redescription and a synonym in the South Asian millipede genus Xenobolus Carl, 1919 (Spirobolida, Pachybolidae) - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2020)
The South Asian spiroboloid species Xenobolus carnifex (Fabricius, 1775) is redescribed and illustrated in detail. The genus Xenobolus Carl, 1919 is diagnosed and its relationship and subfamily placement within Pachybolidae Cook, 1897 are discussed. The species Xenobolus acuticonus Attems, 1936 is synonymised with X. carnifex based on morphological and DNA barcoding data. Information on the natural history of X. carnifex is provided and its current distribution is mapped.